Analysis of Freon Leakage in Condenser to Room Temperature on MT. Kuang: Analisa Kebocoran Freon pada Kondensor terhadap Suhu Ruangan di Kapal MT. Kuang - Ardy, Iqbal Muhammad; Wiweko, Albert; Siregar, Muhammad Sapril; Nurmala, Eka; Syahputra, Dinur (PT. Alpha Trianguli Australis, 2024)
The development of technology has led to increased use of air conditioning. Air conditioning is a process that cools, dries, cleans, and circulates air, while controlling its quantity and quality. It is important for machinists and electricians responsible for cooling machines to effectively carry out their duties and responsibilities by maintaining the machines properly. This research is a qualitative case study involving descriptive analysis using written or spoken observations of behavior. It focuses on the analysis of freon leaks in the condenser related to room temperature on the MT ship, Kuang. The research concludes that the decrease in condenser work in refrigerator machines is caused by interference with the dryer. The recommended efforts include inspecting and repairing leaking pipes, and conducting maintenance and repairs in accordance with the Manual Book standards.